The answer is <span>x - 1 = 3x + 9
All steps are:
</span>Step 1: 4ˣ⁻¹ = 64ˣ⁺³<span>
Step 2: 4</span>ˣ⁻¹ = (4³)ˣ⁺³ <span>
Step 3: 4</span>ˣ⁻¹ = 4³ˣ⁺⁹
Step 4: x - 1 = 3x + 9
Step 5: x - 3x = 1 + 9
Step 6: -2x = 10
Step 7: x = 10/-2
Step 8: x = -5
Answer:145
Step-by-step explanation:x-5+3x+25=180
4x+20=180 4x=160 x=40. <k=120+25=145
Answer:
10 spiders and 12 ants
Step-by-step explanation:
You need to create two equations
s = # of spiders
a = # of ants
s + a = 22 heads
since each spider and ant has one head
8s + 6a = 152 legs
since every spider has 8 legs and every ant has 6
s + a = 22 can be turned into s = 22 - a
now use substitution
8(22 - a) + 6a = 152
176 - 8a + 6a = 152
176 - 2a = 152
24 = 2a
a = 12
now that you have the number of ants you can solve for the number of spiders
s + a = 22
s + 12 = 22
s = 10